Management Accounting Systems and Organizational Performance of Commercial Banks in Nepal - Ballav Niroula (Innovation Business Management and Accounting Journal, 2025)
This study investigates the profound influence of management accounting systems (MAS) on the organizational performance of commercial banks in Nepal. Drawing upon a quantitative research design with a sample of 385 employees from Kathmandu Valley’s commercial banks, the research explores how key MAS components, namely, controlling and reporting, budgeting, decision-making, costing systems, and performance evaluation, collectively impact various dimensions of organizational success. The findings reveal a generally positive perception among employees regarding the effectiveness of these practices. Correlation analysis indicates moderate positive relationships between all management accounting practices and organizational performance, with budgeting demonstrating the strongest association. Regression analysis further confirms that controlling and reporting, budgeting, costing systems, and performance evaluation practices exert a significant positive impact on organizational performance. However, decision-making practices were found to have an insignificant impact within this model. This study presents crucial theoretical and practical implications, emphasizing the need for Nepalese commercial banks to strengthen their management accounting frameworks to improve operational efficiency, strategic decision-making, and competitive positioning in a dynamic financial context.